Val av produktion vid generationsskifte - Månsson, Pernilla (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2004)
The objective of this thesis was to get more knowledge before an alternation of generations. In theses I have chose to make two drawings, one for dairy cows and one for cattle rearing. The drawings are made for a future alternation of generations at my parental home in the province Dalarna. The results are made out of educational visits at different farms and literature investigations. Those dairy farms who I visited had different milking system at each farm and the cattle farm I visited had beef production. The farms are placed in the middle and south of Sweden. At 1998 the Swedish Board of Agriculture decided to change the stall breadth and stall length and the result of this is that many farmers had to rebuild their cattle- and dairy buildings or end farming.